2019
DOI: 10.1080/13603124.2019.1623923
|View full text |Cite
|
Sign up to set email alerts
|

Distributed pedagogical leadership and teacher leadership in early childhood education contexts

Abstract: The topic of distributed pedagogical leadership has attracted researchers' interest in early childhood education leadership. A growing body of research focuses on investigating leadership enacted between leaders and teachers in ECE settings. In this article, we focus on the enactment of distributed pedagogical leadership in Finnish ECE settings and their relations to teacher commitment to pedagogical leadership on staff teams. The study employed an explanatory sequential mixed methods design. Data on the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 22 publications
3
100
1
12
Order By: Relevance
“…Although the middle leaders were initially asked by the principals to become middle leaders, their practices developed from being among the group of middle leaders. But at the same time, each recognised that they were confident in the role and were supported by their colleagues, their principal and other middle leaders, opposite to what Heikka (2014) found in her study where a lack of trust was found between macro and micro levels in directors having difficulties in sharing responsibility for leadership in the organisation. This issue can further be related to the discourse of professional learning communities (Stoll et al 2006) and collegial learning as a way to strengthen knowledge among the teachers which in turn benefit students' learning (Timperley 2012).…”
Section: Concluding Commentscontrasting
confidence: 71%
See 1 more Smart Citation
“…Although the middle leaders were initially asked by the principals to become middle leaders, their practices developed from being among the group of middle leaders. But at the same time, each recognised that they were confident in the role and were supported by their colleagues, their principal and other middle leaders, opposite to what Heikka (2014) found in her study where a lack of trust was found between macro and micro levels in directors having difficulties in sharing responsibility for leadership in the organisation. This issue can further be related to the discourse of professional learning communities (Stoll et al 2006) and collegial learning as a way to strengthen knowledge among the teachers which in turn benefit students' learning (Timperley 2012).…”
Section: Concluding Commentscontrasting
confidence: 71%
“…According to the middle leaders, this kind of peripheral involvement by the principal is not uncommon (see e.g. Heikka 2014). However, one noted that some teachers found it uncomfortable when the principal was present; it was felt that when the principal was absent for any length of time, discussions had a different tone and depth.…”
Section: Principals As Participants Not Leadersmentioning
confidence: 99%
“…In the Finnish context, the directors' expanded areas of responsibility mean that ECE teachers also need to have responsibility for pedagogical leadership (Fonsén and Ukkonen-Mikkola, 2019). Therefore, distributed leadership practices have a crucial role in leading the implementation of the ECE curriculum (Cheung et al, 2019;Heikka, 2014;Kivunja, 2015).…”
Section: Pedagogical Leadershipmentioning
confidence: 99%
“…As defined by McDowall Clark and Murray (2012), this style of leadership is "non-hierarchical, flexible and responsive, enabling leadership to emerge at any level of the organisation wherever the appropriate knowledge and expertise or initiative occurs and with the ability to identify and act on challenges and opportunities" (p.12). Recent research suggests that pedagogical leadership is ineffective when a traditional leader works alone, highlighting the importance of implementing distributed leadership (Heikka and Waniganayake, 2011, Heikka et al, 2013, Heikka, 2014.…”
Section: Theoretical Backgroundmentioning
confidence: 99%